1996
DOI: 10.1037/1040-3590.8.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal problems and the psychotherapy context: The construct validity of the Inventory of Interpersonal Problems.

Abstract: The interpersonal circumplex was used to categorize patients reporting interpersonal distress into 1 of 4 problem quadrants: Friendly Dominant, Hostile Dominant, Hostile Submissive, and Friendly Submissive. At several points in treatment, therapists assessed their patients' personality disturbances, global functioning, and assets and liabilities for therapy. Patients described their in-session experiences using the Therapy Session Report (D. E. Orlinsky & K. I. Howard, 1975). The 4 problem types each had a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
107
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 65 publications
13
107
3
1
Order By: Relevance
“…The results are also consistent with results from nonoffender samples, in which high dominance has been identified as an indicator of problematic response to treatment (e.g., Gurtman, 1996; see also Muran et al, 1994). Whether DOM is associated with actual negative treatment outcomes among offenders (i.e., recidivism), as opposed to staff ratings, is an important question that has yet to be addressed in the literature.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The results are also consistent with results from nonoffender samples, in which high dominance has been identified as an indicator of problematic response to treatment (e.g., Gurtman, 1996; see also Muran et al, 1994). Whether DOM is associated with actual negative treatment outcomes among offenders (i.e., recidivism), as opposed to staff ratings, is an important question that has yet to be addressed in the literature.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Muran, Segal, Samstag, and Crawford (1994) reported that client selfreports of interpersonal features predict subsequent ratings of treatment alliance in short-term cognitive therapy. Similarly, interpersonal features have been shown to predict therapist ratings of personality characteristics and global functioning in the context of brief psychodymamic therapy (Gurtman, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we examined subtype differences on posttreatment measures of general symptom severity, level of social anxiety, psychological well-being, level of optimism, and satisfaction with social functioning. Extensive research using the IIP-C has shown that friendly-submissive interpersonal problems are positively related to psychotherapy outcome, whereas hostile-dominant problems are negatively related to outcome (e.g., Gurtman, 1996;Horowitz et al, 1992;Horowitz, Rosenberg, & Bartholomew, 1993;Kasoff & Pincus, 2002;Muran et al, 1994). Therefore, we predicted that socially phobic patients with friendly, exploitable, and submissive interpersonal problems would respond more positively to psychotherapy than socially phobic patients with avoidant, cold, and hostile interpersonal problems.…”
Section: This Studymentioning
confidence: 99%
“…To address the shortcomings of the "uniformity myth," some researchers have argued for the usefulness of circumplex models of interpersonal behavior (see Gurtman, 1992Gurtman, , 1996Wiggins, 1982). In brief, circumplex models are derived from interpersonal theory (e.g., Carson, 1969;Kiesler, 1983Kiesler, , 1986Kiesler, , 1996Leary; and consist of two orthogonal dimensions: control and affiliation.…”
Section: Circumplex Models Of Interpersonal Functioningmentioning
confidence: 99%